2003
DOI: 10.1191/0959683603hl643rp
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of ostracode assemblages and anthropogenic pollution during the last 100 years, in sediment cores from Hiroshima Bay, Japan

Abstract: Temporal changes of ostracodes during the last 100 years observed in three sediment cores from Hiroshima Bay, the Seto Inland Sea, Japan, provide valuable information about influences on ostracodes caused by anthropogenic pollution. This is the first detailed report of historical records of the relationship between ostracodes and pollution established from core samples drilled in the polluted inner bay. At least 38 ostracode species were identified from 40 samples. Based on biofacies, the density of ostracodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 13 publications
1
25
0
3
Order By: Relevance
“…Rather surprisingly, these 100-200-yr sediment records revealed no major changes in ostracod diversity at any of the four stations in Osaka Bay. Yasuhara et al (2003) reported similar patterns in Hiroshima Bay. Ostracod abundances decreased from the 1940s in the inner bay while the relative abundance of B. bisanensis increased and diversity remained relatively stable over the 100-yr record.…”
Section: Benthic Ostracodasupporting
confidence: 64%
See 3 more Smart Citations
“…Rather surprisingly, these 100-200-yr sediment records revealed no major changes in ostracod diversity at any of the four stations in Osaka Bay. Yasuhara et al (2003) reported similar patterns in Hiroshima Bay. Ostracod abundances decreased from the 1940s in the inner bay while the relative abundance of B. bisanensis increased and diversity remained relatively stable over the 100-yr record.…”
Section: Benthic Ostracodasupporting
confidence: 64%
“…Over shorter time scales, oscillations in the diversity of the two taxa show some correspondence, although the match is not precise. As mentioned above, ostracod abundance in Osaka Bay began to decline at the innermost, hypoxia-influenced station (OBY) around 1910-1920 while diversity remained stable (Yasuhara et al, 2007). In the same core, foraminiferans increased in abundance from ∼1920 to ∼1965 before undergoing a relatively modest decrease (Tsujimoto et al, 2006b), while diversity decreased substantially after ∼1920.…”
Section: Benthic Ostracodamentioning
confidence: 91%
See 2 more Smart Citations
“…Seventeen percent (1171 out of 6767 total specimens) were living. Ostracode biotopes were determined by Q-mode cluster analysis based on Horn's overlap index (Horn 1966) and the unweighted pair group method with arithmetic mean (UPGMA: Sneath and Sokal 1973), which have been successfully applied for ostracode faunal analysis (e.g., Yasuhara et al 2003;Irizuki et al 2004;Yasuhara et al 2004), using PAST ver. 1.38b (http://folk.uio.no/ohammer/past/; Hammer et al 2001).…”
Section: Ostracode Biotopesmentioning
confidence: 99%